THE PROBLEM QUESTIONS OF TEACHING «SAFETY OF LIFE» IN UKRAINIAN UNIVERSITIES - Опара, Н. М. (Scientific Progress & Innovations, 2015)
The current issues of teaching of the courses «Safety of life», «Occupational safety», «Civil protection», «Safety in industry» are presented in the article. We made the analysis of recent scientific publications on the subject, consider issues that arise during the transformation of the study above mentioned disciplines from the regulatory category in the category of «choice»; it is shown possible ways of their elimination.